Clinical characteristics of patients with Rutherford category IV, compared with V and VI. (21st July 2015) - Tsuchiya, Taketsugu; Iida, Osamu; Shiraki, Tatsuya; Soga, Yoshimitsu; Hirano, Keisuke; Suzuki, Kenji; Yamaoka, Terutoshi; Miyashita, Yusuke; Kitayama, Michihiko; Kajinami, Koji
Objective: Patients categorized Rutherford category IV might have different characteristics compared with Rutherford category V and VI. Our study aims were to estimate the clinical differences between Rutherford category IV and Rutherford category V and VI, for those underwent endovascular therapy for isolated infrapopliteal disease, and also to find risk factors for endovascular therapy in Rutherford category IV. Methods: Based on the Japanese multi-center registry data, 1091 patients with 1332 limbs (Rutherford category IV: 226 patients with 315 limbs, Rutherford category V and VI: 865 patients with 1017 limbs) were analyzed retrospectively. Results: Patients' backgrounds and lesions' characteristics had significant differences. Both freedom rate from major adverse limb event with perioperative death and amputation-free survival rate at 1 year were better in Rutherford category IV than Rutherford category V and VI (93.6% vs 78.3%, 87.7% vs 66.7%) and those maintained to 3 years ( p < 0.0001). Significant predictors for major adverse limb event/perioperative death were small body mass index (<18.5 kg/m 3 ) and initial endovascular therapy success, and those for amputation-free survival were small body mass index (<18.5 kg/m 3 ), non-ambulatory status, high systematic inflammatory reaction (C-reactive protein > 3.0 mg/dL), chronic obstructive pulmonary disease, and coronary artery disease in Rutherford category IV. Conclusion: From the present results, Rutherford category IV should be recognized to have quite different backgrounds and better outcome from Rutherford category V and VI.